2016
DOI: 10.5194/tc-10-523-2016
|View full text |Cite
|
Sign up to set email alerts
|

Recent summer sea ice thickness surveys in Fram Strait and associated ice volume fluxes

Abstract: Abstract. Fram Strait is the main gateway for sea ice export out of the Arctic Ocean, and therefore observations there give insight into the composition and properties of Arctic sea ice in general and how it varies over time. A data set of ground-based and airborne electromagnetic ice thickness measurements collected during summer between 2001 and 2012 is presented here, including long transects well into the southern part of the Transpolar Drift obtained using fixedwing aircrafts. The primary source of the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(130 citation statements)
references
References 36 publications
(84 reference statements)
11
116
3
Order By: Relevance
“…This period is chosen to match the satellite period. Sea ice thickness used in this study is the sea ice volume per grid cell area taking into account open water (named "sivol" according to SIMIP nomenclature) rather than the actual thickness Krumpen et al (2016) 1980-2012: significant positive trend Smedsrud et al (2016) Increase Wind 1979-2014:…”
Section: Model and Sensitivity Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This period is chosen to match the satellite period. Sea ice thickness used in this study is the sea ice volume per grid cell area taking into account open water (named "sivol" according to SIMIP nomenclature) rather than the actual thickness Krumpen et al (2016) 1980-2012: significant positive trend Smedsrud et al (2016) Increase Wind 1979-2014:…”
Section: Model and Sensitivity Experimentsmentioning
confidence: 99%
“…However, a distinction needs to be made between area and volume exports: area export is the product of sea ice drift speed, concentration and transect length, while volume export is the product of area export and ice thickness. Several studies show an increase of ice area export at Fram Strait since the late 1970s (Langehaug et al, 2013;Krumpen et al, 2016;Smedsrud et al, 2016), while Kwok et al (2013) show a small decrease between 1982 and 2009. In terms of volume export, the amount of studies is limited by the relatively low ice thickness temporal coverage at Fram Strait.…”
Section: Introductionmentioning
confidence: 99%
“…Positive trends were also found in the annual FS ice area export by Widell et al (2003) (4 % per decade from 1950 to 2000) and Smedsrud et al (2011Smedsrud et al ( ) (5 % per decade from 1957Smedsrud et al ( to 2010. Using the available NSIDC sea ice drift data, Krumpen et al (2016) recently found a much higher trend for 1980-2012 (37.6 % per decade) but noted that the large positive trend seemed "unrealistic". However, contrary to these studies, Kwok et al (2013) found a small negative trend in annual FS ice area export between 1982 and 2009, but with positive trends for [2001][2002][2003][2004][2005][2006][2007][2008][2009] for both annual (October-September) and summer (June-September).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with ice drift information obtained from Environmental Satellite (ENVISAT) synthetic aperture radar (SAR) images and long-term moorings equipped with acoustic Doppler current profilers (ADCP) have shown that accuracy of the of IFREMER motion data is high and the uncertainty in the ice area export is around 81 × 10 3 km 2 for the NB and 57 × 10 3 km 2 for the EB over the entire winter (OctoberMay) (Rozman et al, 2011;Krumpen et al, 2013). For more detail about the applied ice drift and concentration products we refer to Ezraty et al (2007), Girard-Ardhuin and Ezraty (2012), Krumpen et al (2016).…”
Section: Satellite-based Ice Area Exportmentioning
confidence: 99%
“…Flaw polynyas are open water sites between pack ice and fast ice of high net ice production sustained by winds. For a detailed description of the HEM principle we refer to (Haas et al, 2009;Krumpen et al, 2016). In short, the instrument that is towed by a helicopter 15 m above the ice surface utilizes the contrast of electrical conductivity between sea water and sea ice to determine its distance to the ice-water interface.…”
Section: Airborne Ice Thickness Datamentioning
confidence: 99%